Pelatihan Pembuatan Pupuk Organik Eceng Gondok sebagai Pemanfaatan Tanaman Gulma di Desa Telukbango Kabupaten Karawang - Nurhanifah, Afifa; Alamsyah, Vikram; Sadidan , Ikhwanussafa (Jurnal Abdimas Perbanas, 2024)
Hyacinth is one of the weed plants or nuisance plants that grow a lot in Telukbango Village, Batujaya District, Karawang. The purpose of this community service activity in tandem with the Singaperbangsa University Karawang Student Real Work Lecture program is to increase the knowledge and insight of the people of Telukbango Village on the process of utilizing water hyacinth plants. Hyacinths are used as basic ingredients for making organic fertilizer because the amount is very large and has the potential to become waste that hampers agricultural irrigation channels. Training on making hyacinth organic fertilizer is carried out by lecture method, distributing leaflets on the stages of making hyacinth organic fertilizer, and joint practice of making fertilizer. The result of this community service activity is that the people of Telukbango Village, especially farmers, understand the use of water hyacinths and the process of making fertilizer from water hyacinths which so far only has the potential as waste. The farmers and the community present enthusiastically welcomed the use of water hyacinth into organic fertilizer, which was supported by all levels of Telukbango Village officials.